Rekontruksi Konsep Bai’ Al-’Inah dan Relevansinya terhadap Pengembangan Produk Keuangan Syariah Modern - Tegar Efrizal; Muhamad Zen (Fakultas Syariah IAIN Kerinci, 2025)
Bai' al-'Inah is a concept in muamalah fiqh that still causes incidents, especially in modern sharia financial practices. Formally, this transaction takes the form of two valid sale and purchase contracts, but substantially it is often seen as resembling an interest-bearing loan, thus potentially containing elements of usury. This study aims to analyze Bai' al-'Inah comparatively between the views of classical scholars, especially Imam al-Syafi'i in al-Umm and Ibn Taymiyyah in Majmū' al-Fatāwā, and contemporary fatwas of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI), especially Fatwa No. 04/DSN-MUI/IV/2000 and Fatwa No. 31/DSN-MUI/VI/2002. This study uses a qualitative method with a library research approach, through thematic analysis of relevant classical and contemporary literature. The results of the study indicate that Imam al-Syafi'i tends to allow Bai' al-'Inah formally as long as the pillars and conditions of the contract are fulfilled without any hidden conditions, while Ibn Taymiyyah firmly rejects the practice of being divided because it is a usury that deviates from the maqasid al-syariah. Meanwhile, the DSN-MUI implicitly rejects Bai' al-'Inah in Islamic financial practices in Indonesia, although in certain contexts it allows mechanisms that resemble Bai' al-'Inah on the basis of greater public interest considerations. This study confirms that Bai' al-'Inah is not only a matter of formal legality, but also a moral, social, and ethical issue in the Islamic financial system. Thus, the development of modern Islamic finance should not stop at the formal fulfillment of the contract, but also focus on containing the maqasid al-syariah in order to realize justice and economic welfare.